Japan talks - Lahiri, Amar (Hokuseido Press, 1940)
Those seeking high literaty and academic merits in this olume no doubt will br disappointed because, as a matter of fact journalist. Those who are inquisitive about things Japanese perhaps will gather some food for appeasing, to a certain extent, their hunger for this human touch.